Are vertical linkages promoting the creation of a mining cluster in Chile? An analysis of the SMEs' practices along the supply chain. (February 2016) - Atienza, Miguel; Aroca, Patricio; Stimson, Robert; Stough, Roger
In regions whose industrial structure is organized around one or more large firm corporations, the best practices of small and medium enterprises depend on where firms are located in the supply chain. This paper studies 351 small and medium enterprises in the Antofagasta Region in Chile between 2007 and 2008, where multinational and public mining companies are the drivers of the local economy and the government is promoting the formation of a mining cluster. Structural equation model is used to show that first-tier small and medium enterprise mining suppliers, directly related to large corporations, follow business practices that promote international certification, quality control, and investment in innovation, while in contrast second-tier small and medium enterprises are more focused on avoiding insolvency and client orientation. These results cast doubt on the formation of a mining cluster in the region and suggest the need for differentiated policies in these two groups of small and medium enterprises, especially those related to knowledge transfer.